Energy Absorption Behaviour Of r-PET/Epoxy Laminated Composite with Varying Matrix Ratio in Quasi-Static Indentation Test - Azman, Asyran Muhammad; Azrin Hani Abdul Rashid; Nurul Zakiah Zamri Tan (Progress in Engineering Application and Technology, 2022)
The strip of recycled Polyethylene Terephthalate (r-PET) bottle waste used as a reinforcement in polymer composites for impact energy absorption application is little recognized. This study investigates the energy absorption behaviour of r-PET/Epoxy laminated composite with varying matrix ratios subjected to quasi-static indentation test. The r-PET bottle strip orientation was arranged to cross-ply structure to produce the laminated composite. Different epoxy and hardener ratio for the laminated composite was applied which are, 8:1, 7:1, 6:1, 5:1, and 4:1. The r-PET / Epoxy laminated composites were developed using hand-layup method. Grooveless r-PET bottles were selected to produce the r-PET strip and the strips were turned into cross-ply mats. The quasi-static indentation test was conducted to measure the maximum indentation force and total energy absorption of r-PET /Epoxy laminated composite. After the indentation test, the impact damage at front and rear surfaces was visually analysed. The findings show that different epoxy and hardener ratio affect the indentation performance of the r-PET / Epoxy laminated composite. This study evidenced the cross-ply r-PET / Epoxy laminated composite with the epoxy and hardener ratio of 6:1 has better indentation performance. The maximum indentation force and energy absorption were also improved drastically.